Development of E-Office Information System in Administration Faculty of Engineering, State University of Padang - Elsa Sabrina; Dedy Irfan; Asrul Huda (Universitas Pendidikan Mandalika, 2022)
Office management plays a very important role in an organization or institution that provides many information and data management services. As a result, management services often have time, energy, and cost inefficiencies. Therefore, we need an information system that can support the management process so that it can be executed effectively and efficiently. The method used to develop this system is the method of software development using the DevOps (Development and Operations) development model. This model consists of several stages including the planning stage, the needs analysis stage, the design stage and the implementation stage. This model allows system administrators to integrate with IT professionals during the system development process. This system architecture is based on Model-View-Controller, which uses the Yii2 framework in the PHP programming language. The result of this final project is the creation of an E-Office information system that includes several services such as human resources and student affairs. This information system is expected to reduce problems and improve the process of government services.